2011 Lo último que se puede esperar - Grupo La noche en vela (2017)
Actúan: Horacio Acosta, Carolina Adamovsky, José Luis Arias, Laura Battaglini, Monica Dreidemie, Víctor Galestok, Adriana Garibaldi, Nani López, Natalia Olabe, Alejandro Sánchez, Adrián Silver, Mariana Tognetti | Escenografía: Félix Padrón | Asistencia artística: Alejandro Barratelli | Dirección: Paco Giménez | Compañía: La Noche En Vela | Consultado el 5 de agosto de 2017 | http://www.alternativateatral.com/obra19768-lo-ultimo-que-se-puede-esperar